1996
DOI: 10.1002/eji.1830261122
|View full text |Cite
|
Sign up to set email alerts
|

Definition of the mitogenic factor (MF) as a novel streptococcal superantigen that is different from streptococcal pyrogenic exotoxins A, B, and C

Abstract: Human T cell activation by recombinant mitogenic factor (rMF) was investigated in comparison with that by recombinant streptococcal pyrogenic exotoxins (rSPE) A, B, and C. Recombinant MF, rSPEA, and rSPEC were mitogenic for peripheral blood mononuclear cells (PBMC), whereas rSPEB was not. Recombinant MF required only HLA-DR for the stimulation of PBMC, as determined using monoclonal antibodies (mAb) to HLA class II molecules and the mouse L cells transfected with HLA class II molecules. Recombinant SPEA and rS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 38 publications
(15 reference statements)
1
32
0
Order By: Relevance
“…We conclude that the tiny amounts of SMEZ present in culture supernatants from H293, calculated by bioassay to be ϳ5 pg/ml, are largely responsible for the mitogenic activity of this strain. Native preparations of a wide range of streptococcal proteins, including M protein, SPEA, SPEB, and MF were previously reported to selectively stimulate human T cells bearing TCR V␤8 (11)(12)(13)(14)(15). More recently a previously unknown streptococcal superantigen, SPEX (identical to SMEZ) was shown to underlie the potent stimulation of human V␤8 ϩ T cells attributed to SPEB and MF (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…We conclude that the tiny amounts of SMEZ present in culture supernatants from H293, calculated by bioassay to be ϳ5 pg/ml, are largely responsible for the mitogenic activity of this strain. Native preparations of a wide range of streptococcal proteins, including M protein, SPEA, SPEB, and MF were previously reported to selectively stimulate human T cells bearing TCR V␤8 (11)(12)(13)(14)(15). More recently a previously unknown streptococcal superantigen, SPEX (identical to SMEZ) was shown to underlie the potent stimulation of human V␤8 ϩ T cells attributed to SPEB and MF (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that PBMC of healthy donors was stimulated by mitogenic factors rSPE-A and rSPE-C (16) and that rSPE-C selectively stimulated TCRBV2-or TCRBV6S5-bearing T-cells when the donor had HLA-DRB1*0901 (16). In …”
Section: Stimulation Of Selected Tcrbv-bearing T-cells By Rspe-amentioning
confidence: 99%
“…We previously reported selective expansion of TCRBV2 and TCRBV6S5 after in vitro stimulation of T-cells with recombinant streptococcal pyrogenic exotoxin-C (SPE-C) (16). We also reported polyclonal expansion of TCRBV2 and TCRBV6S5-bearing T-cells in patients in the acute phase of KD but not in those in the convalescent phase of KD or in age-matched controls (17).…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…SPEs have many biological activities such as pyrogenicity, mitogenicity, enhancement of susceptibility to endotoxin shock and suppression of immunoglobulin M production (3). Besides three serologically distinct SPEs, (SPEA, SPEB and SPEC), SSA (13) and MF (14,18) have been reported as a group of superantigens, and the nucleotide sequences of the genes that encode them have been determined (7,8,10,15,19). Superantigens from Streptococcus pyogenes, toxic shock syndrome toxin 1 (enterotoxins A to E) and exofoliative toxins A and B from Staphylococcus aureus comprise a family of superantigens that stimulate T cells by crosslinking different parts of the T-cell receptor with major histocompatibility class II molecules in accessory cells (4-6, 9, 12, 20).…”
mentioning
confidence: 99%